2016
DOI: 10.1002/ece3.2164
|View full text |Cite
|
Sign up to set email alerts
|

Harvested populations are more variable only in more variable environments

Abstract: The interaction between environmental variation and population dynamics is of major importance, particularly for managed and economically important species, and especially given contemporary changes in climate variability. Recent analyses of exploited animal populations contested whether exploitation or environmental variation has the greatest influence on the stability of population dynamics, with consequences for variation in yield and extinction risk. Theoretical studies however have shown that harvesting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…In our experiment, similar to findings by Cameron et al. () for S. berlesei , the effect of harvesting on life stage counts depended on the colour of the environmental noise. In all environments, large‐adult harvesting reduced the mean adult counts; however, in red environments, in contrast to the blue or white environments, this reduction in adult counts did not carry over to reduce egg and juvenile counts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our experiment, similar to findings by Cameron et al. () for S. berlesei , the effect of harvesting on life stage counts depended on the colour of the environmental noise. In all environments, large‐adult harvesting reduced the mean adult counts; however, in red environments, in contrast to the blue or white environments, this reduction in adult counts did not carry over to reduce egg and juvenile counts.…”
Section: Discussionsupporting
confidence: 92%
“…One general pattern that has emerged is how noise colour interacts with density dependence (Kaitala et al., ): a population with undercompensating growth reacts slowly to environmental changes, whereas overcompensating populations overshoot their equilibrium after a perturbation. Bulb mite population growth has been characterised as overcompensating (Cameron & Benton, ; Cameron et al., ). We found that the type of compensating response in the mite populations to the single harvesting rate that we investigated was an interaction between noise colour and harvesting rate, as compensation to harvesting in terms of population growth was not achieved, thus showing undercompensation.…”
Section: Discussionmentioning
confidence: 99%
“…Unraveling the drivers of population growth in variable environments is critical for answering eco‐evolutionary questions (Ruokolainen, Linden, Kaitala, & Fowler, ; Smallegange, Deere, & Coulson, ; Tuljapurkar, ), developing conservation management strategies (Clark, ; Metcalf & Koons, ), predicting the time course of epidemics (Chaves, Scott, Morrison, & Takada, ; Keeling & Gilligan, ) and in influencing the yield of harvested populations (Cameron et al, ; Higgins, Hastings, Sarvela, & Botsford, ; Smallegange & Ens, ). Both demographic processes and temporal variation in environmental conditions are important drivers of population growth (Higgins et al, ; Lande, Engen, & Sæther, ; Turchin & Taylor, ).…”
Section: Introductionmentioning
confidence: 99%
“…This finding has been further discussed by Sugihara et al (). Recently, Cameron et al () experimentally tested the hypothesis of enhanced fluctuations in population size when adult/old individuals were removed using a terrestrial species, the soil mite ( Sancassania berlese ). The experiment consisted of different harvesting treatments under different regimes of environmental fluctuations.…”
Section: Harvest Effects On Age/size Structurementioning
confidence: 99%
“…Seasonal migration is a widespread phenomenon in vertebrates, Only when environmental variation and harvesting were combined did we see strong evidence of magnified fluctuations in abundance." Cameron et al, 2016 being observed in fish, birds and mammals (Milner-Gulland, Fryxell, & Sinclair, 2011). Migration patterns can be culturally transmitted through social learning in both marine (Corten, 2002) and terrestrial environments (Jesmer et al, 2018).…”
Section: Harve S T Effec Ts On S Patial Dis Tributionmentioning
confidence: 99%